Composing Processes: An Overview - Bizzell, Patricia (Academic Discourse and Critical Consciousness, 1992)
Composition scholars agree that the composing process exists or, rather, that there is a complex of activities out of which all writing emerges. We cannot specify one composing process as invariably successful. Current research in the field is beginning to draw a detailed picture of these composing processes. “Composing” usually refers to all the processes out of which a piece of written work emerges. During composing, the writer may spend some time musing, rereading notes or drafts, or reading the texts of others, as well as actually putting words on the page herself. In composition research, “writing” usually refers precisely